2015
DOI: 10.1021/ac503756f
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Enumeration of Gold Nanomaterials at the Single-Particle Level

Abstract: In this study, we developed a highly sensitive automatic counting method for gold nanomaterials at the single particle level, which can serve as a general sensing platform based on counting of gold nanomaterials. This method substantially improved the sensitivity and accuracy for AuNP counting by adopting the color image processing based on the distinctive localized plasmonic light-scattering of gold nanomaterials. The 60-nm AuNPs, with concentrations down to 4 fM, can be detected with our method. As a univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…[16], imaging method [17,18] and some commercial method [19]. UV-Vis absorption spectroscopy is an indirect method for determination of GNP concentration based on the molar absorption coefficient of GNP, which was obtained by measuring GNP size by TEM and gold content of GNP solution by AAS (MS or AES).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16], imaging method [17,18] and some commercial method [19]. UV-Vis absorption spectroscopy is an indirect method for determination of GNP concentration based on the molar absorption coefficient of GNP, which was obtained by measuring GNP size by TEM and gold content of GNP solution by AAS (MS or AES).…”
Section: Introductionmentioning
confidence: 99%
“…However, this method cannot be used in vitro and in vivo studies like AES-TEM method and UV-Vis spectroscopy. Recently, Xu et al reported a single particle counting method for quantification of gold nanoparticles based on dark field light-scattering imaging and color image processing [18]. This method is an indirect procedure for determination of GNP in solution as well.…”
Section: Introductionmentioning
confidence: 99%
“…Then, excess sulfuric acid was added to the tube. Owing to the low pH value, almost all sulfides form H 2 S molecules rather than HS − or S. 2–49 The low solubility made the H 2 S molecule volatilize and come into contact with AuNPs-N 3 -Alk and further reduced the azido group to an amino group, which has been proven by many works. 50–53 Therefore, the cuprous-catalysed click chemistry reaction was blocked, resulting in single AuNPs in the solution.…”
Section: Resultsmentioning
confidence: 98%
“…Nowadays, high-pass output of the scattering image 36 , 37 has become an effective strategy to obtain a new related image in which the useful information is retained and the useless information is deducted. A notable advantage of the high-pass output strategy is the high information fidelity, which is always distorted in the background subtraction process by simple contract adjustment, although a high signal to noise ratio might be obtained (Fig.…”
Section: Resultsmentioning
confidence: 99%